IMPLEMENTASI KEBIJAKAN PEMBANGUNAN DAERAH PROVINSI BENGKULU BERDASARKAN ILMU PENGETAHUAN DAN TEKNOLOGI - Evi Lorita (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
To achieve national aspirations to protect the whole Indonesian and the entire country of Indonesia, promote the commonweal, and educate the nation, the unitary state of Indonesia is divided into small government that has freedom to run the regional autonomy, including in the development of science and technology. Unfortunately, the development of science and technology has not run optimally, as happened in Bengkulu province. This research was a qualitative descriptive study which wanted to see the agenda of Bengkulu’s Government in relation to regional policy framework for science and technology. Data were collected through interviews, observation and documentation. Data was analyzed by using qualitative data analysis Spradley models which was brought into line to the data analysis techniques in the research stage. The results showed that the regional development of science and technology policy for Bengkulu Province has two agenda namely science and technology to pave the backwardness and science and technology for prosperity. Those agendas were focused on the field of food security, energy, technology and transportation management, information and communication technology, security and defense technology, medical technology and medicine, and technology management of natural resources and the environment.Keywords: Autonomy, National Aspirations, Science And Technology Development, Indonesia